The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.18632/oncotarget.14203
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of circulating tumor cells from lung cancer patients with multiple biomarkers using high-performance size-based microfluidic chip

Abstract: Circulating tumor cells (CTCs) have attracted pretty much attention from scientists because of their important relationship with the process of metastasis. Here, we developed a size-based microfluidic chip containing triangular pillar array and filter channel array for detecting single CTCs and CTC clusters independent of tumor-specific markers. The cell populations in chip were characterized by immune-fluorescent staining combining an epithelial marker and a mesenchymal marker. We largely decreased the whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…To demonstrate the suitability of our method for real clinical samples, we replaced the Sgc8c aptamer and the TD05 aptamer with the Lc-17 aptamer and the AP-1 aptamer to target two CTCs with abnormal expression of vimentin and with abnormal expression of cytokeratin (CK) respectively in lung cancer patients. 38,[74][75][76] Aer CTCs were captured by our platform, Cu 2+ and Mg 2+ were added to release CTCs successively. The released CTCs by Cu 2+ or Mg 2+ and unreleased CTCs were collected separately for immunouorescence staining.…”
Section: Ctc Isolation From Cancer Patients' Blood Samplesmentioning
confidence: 99%
“…To demonstrate the suitability of our method for real clinical samples, we replaced the Sgc8c aptamer and the TD05 aptamer with the Lc-17 aptamer and the AP-1 aptamer to target two CTCs with abnormal expression of vimentin and with abnormal expression of cytokeratin (CK) respectively in lung cancer patients. 38,[74][75][76] Aer CTCs were captured by our platform, Cu 2+ and Mg 2+ were added to release CTCs successively. The released CTCs by Cu 2+ or Mg 2+ and unreleased CTCs were collected separately for immunouorescence staining.…”
Section: Ctc Isolation From Cancer Patients' Blood Samplesmentioning
confidence: 99%
“…A number of microfluidics‐based technologies have been developed for CTC isolation and biomimicking of tumor microenvironment to evaluate cancer metastasis. Although the capture efficiency can reach 98% with purity of 89% [87] and throughput can reach 3 mL/min [75] for CTC isolation using microfluidic technologies, the performance of these methods is not good enough and still needs further improvement. To better meet the clinical requirements of CTC detection, the technology should tend to the following demands: (a) higher isolation efficiency which may need new technologies or combination of several technologies; (b) specificity verification strategies to prove that the isolated targeted cells are real CTCs which have clinical significance; (c) accuracy and repeatability that apply automated apparatus as much as possible without much intervention from human operators; (d) operability and generalizability; (e) fully heterogeneity consideration to distinguish different CTC subpopulations; and (f) clinical demonstration to prove this technology is useful in clinical trials.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Recently Gao et al modified an earlier reported size based CTC isolation technology (Huang et al, 2014), which not only improved the device performance but also helped in sequential capture of CTM and CTC separately (Gao et al, 2016). The earlier version of device made use of a series of alternating and parallel microchannels; main channel and side channel, connected to each other through an array of filter channels at regular intervals.…”
Section: Microfluidic Chip With Triangular Pillar Array and Filter Chmentioning
confidence: 99%
“…(i) Bulk filtration (and CTM separation) through two successive sub-regions of triangular micropost array with variable narrowing channel widths (ii) CTC separation through a series of alternating and parallel microchannels (Gao et al, 2016) interconnected through an array of filtered channels (Sarioglu et al, 2015) CTM traverse capillary sized vessels by reversibly reorganizing in to singlefile chain-like geometries (Au et al, 2016)…”
Section: Microfluidic Chip With Tandem Triangular Pillar and Filter Cmentioning
confidence: 99%